Safety of Tocilizumab in Rheumatoid Arthritis Patients with Resolved Hepatitis B Virus Infection: Data from Real-World Experience - Ahn, Sung Soo; Jung, Seung Min; Song, Jason Jungsik; Park, Yong-Beom; Park, Jun Yong; Lee, Sang-Won (Yonsei medical journal, 2018)
To investigate whether the use of IL-6 receptor antagonist (tocilizumab) might be associated with hepatitis B virus (HBV) reactivation in rheumatoid arthritis (RA) patients, particularly in those with resolved HBV infection [HBV surface antigen (HBsAg) negative and antibody to HBV core antigen (anti-HBc) positive, serologically]. HBsAg, anti-HBc, antibody to HBsAg (anti-HBs), and HBV DNA titers were measured in RA patients who had continuously received tocilizumab for more than 3 months. Patients were divided into two groups according to the presence of anti-HBc. Clinical and laboratory data, in addition to medications administered along with tocilizumab during the treatment duration with tocilizumab, were compared between the two groups. HBV reactivation was defined as the presence of HBV DNA in sera, and alterations in HBsAg, anti-HBc, and anti-HBs titers according to the use of tocilizumab were also evaluated. Fifteen of 39 patients (38.5%) had anti-HBc positivity, while 24 patients (61.5%) did not. There were no differences in demographic data, serologic classification, and variables related to tocilizumab between the anti-HBc-positive and -negative groups. Comparison of the medications administered along with tocilizumab treatment revealed no meaningful differences. None of the patients experienced reactivation of HBV. In addition, in 15 patients with resolved HBV infection, no alterations in HBsAg, anti-HBc, and anti-HBs titers were observed with the use of tocilizumab. Tocilizumab may be applied to RA patients safely with few concerns for HBV reactivation, particularly in those with resolved HBV infection.